2020
DOI: 10.3390/s21010138
|View full text |Cite
|
Sign up to set email alerts
|

A Fibre-Optic Platform for Sensing Nitrate Using Conducting Polymers

Abstract: Monitoring nitrate ions is essential in agriculture, food industry, health sector and aquatic ecosystem. We show that a conducting polymer, poly(3,4-ethylenedioxythiophene) (PEDOT), can be used for nitrate sensing through a process in which nitrate ion uptake leads to oxidation of PEDOT and change of its optical properties. In this study, a new platform is developed in which a single-mode fibre coated at the tip with PEDOT is used for nitrate sensing. A crucial step towards this goal is introduction of carbona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Exploiting the concomitant change in PEDOT optical properties with change in its electrical properties, Shahnia et al demonstrated a nitrate sensor consisting of VPP PEDOT:Tos deposited at the end of an optical fibre. 43 Through control of the oxidant deposition process, 44 PEDOT:Tos was fabricated at the tip of optical fibres of diameters on the order of 100 mm. Rather than using electrochemical techniques to reduce the PEDOT:Tos, a chemical reduction process was employed based on complementary work by Sethumadhavan et al 45 The optical fibre sensor was used as a dip probe and shown to simply measure the nitrate concentration in the electrolyte at concentrations relevant for applications such as water treatment and fertigation in agriculture.…”
Section: Sensingmentioning
confidence: 99%
“…Exploiting the concomitant change in PEDOT optical properties with change in its electrical properties, Shahnia et al demonstrated a nitrate sensor consisting of VPP PEDOT:Tos deposited at the end of an optical fibre. 43 Through control of the oxidant deposition process, 44 PEDOT:Tos was fabricated at the tip of optical fibres of diameters on the order of 100 mm. Rather than using electrochemical techniques to reduce the PEDOT:Tos, a chemical reduction process was employed based on complementary work by Sethumadhavan et al 45 The optical fibre sensor was used as a dip probe and shown to simply measure the nitrate concentration in the electrolyte at concentrations relevant for applications such as water treatment and fertigation in agriculture.…”
Section: Sensingmentioning
confidence: 99%
“…This was determined by measuring the electrical and optical property changes of the PEDOT nanofilms. Shahnia et al 73 leveraged this research to combine vapour deposited PEDOT nanofilms onto the end of optical fibres to detect NO 3 − in water with a view to expanding the sensing range to NO 3 − concentrations in aquatic ecosystems.…”
Section: Pedot In the Environmentmentioning
confidence: 99%
“…Current methods for nitrate detection include spectrometers, electrochemical sensors, chromatography, and capillary electrophoresis [5][6][7][8][9][10]. There are numerous advantages to using these devices, including high accuracy, resolution, and excellent repeatability.…”
Section: Introductionmentioning
confidence: 99%
“…Through analyzing samples with various properties, they suggested that the sensitivity of the nitrate uptake is dependent on the chain ordering in [x00] plane, surface morphology, electrical conductivity, and charge transport [35]. Later, Shahina et al demonstrated that PEDOT could detect nitrate via a change in optical properties because of the oxidation of PEDOT [5]. The proposed platform exhibits the change in the optical behavior of the PEDOT layer at the tip of the fiber as it experiences chemical oxidation and reduction [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation